Ownership Structure and CEO Compensation: Evidence from Jordan - Al-Al-Msiedeen, Jebreel Mohammad; Al Sawalqa, Fawzi A (Asian Economic and Financial Review, 2021)
The current study examines the effect of ownership structure (i.e., government ownership, family ownership, and foreign ownership) on chief executive officer (CEO) compensation in an emerging market, by considering Jordan as a case study. By using a sample of 136 non-financial firms listed on the Amman Stock Exchange over the period of 2015–2019, we find that family ownership has a positive and significant impact on CEO compensation. The finding regarding foreign ownership is contrary to expectations, with a higher foreign ownership reflecting a higher CEO compensation. Overall, these results imply that the ownership structure of Jordanian companies exerts a significant influence on the CEO pay setting process. However, government ownership has no relationship with CEO compensation. This indicates that government ownership is ineffective in determining CEO compensation. We further find that firm size is positively related to CEO compensation, indicating that larger companies have more ability to generate high internal funding, and can afford to pay higher compensation to quality managerial talent. In contrast, the effects of firm age and liquidity are not at significant levels.